Glimpse of Sports in Chhara Village of Haryana: Exploring the Rise of Sports in Chhara Village (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This research is done to understand the dynamic of sports among the youth in Chhara village of Jhajjar district of Haryana, how this village is blossoming as the breeding ground for sports. In the research paper focus is on the environment in village among the youth, how they are taking up sports as a activity, as a platform to get government jobs, to bring accolades for nation by competing at highest level in world sports arena.